Financiamento da política pública para a educação profissional no Estado do Paraná (2003-2012) - Bosio, Queila Franciéle Fabris (2013)
This study aims to analyze the financing of public policy and management of professional education in the state of Paraná in the period 2003 to 2012, covering the resumption of professional education, the integration with the high school and the resources planned and carried out for this modality in this period. For purposes of methodology we used primary survey of theoretical foundations in the laws, decrees and resolutions as secondary and theoretical sources we used articles and journals related to the topic. Analyses of financing are presented through graphs and tables , which include the predicted values of the public budget to finance public policy professional education for ten years in confrontation values made by the State of Paraná , these monetarily restated by INPC / IBGE reference 12/2012 , so there are no inflationary distortions . According to the proposed research , we can consider that even with the resumption of discourse prioritizing professional teaching , and investments in this area , it was observed that these resources are scarce , and include the minimum required , without taking as basis the real quality , but the minimum quality , ideological influences were also identified in the propositions of professional education for the period , sometimes with mild discourses to capitalism and relations of market work , sometimes with more pronounced discourses . It was concluded that professional education needs to become in fact a public education policy, with its own funding and not depend only on political will and government programs